Evaluación emancipatoria del teletrabajo en los establecimientos de salud de Segundo Nivel de la ciudad de Loja, período 2020-2022. - Morocho Lapo, Valeria Estefany (2024)
The present research work entitled "Emancipatory evaluation of teleworking in Second Level health facilities in the city of Loja, period 2020-2022” focuses on evaluating the public policy of telework from an emancipatory perspective with three key objectives. First, it analyzes the normative instruments of teleworking, such as the Organic Law of Humanitarian Support, issued in Ecuador during the aforementioned period, providing a solid context for understanding the results. Second, it characterizes the actors involved, including public servants, workers, and users of health facilities, to understand their perspectives and needs. Third, it designs and implements an emancipatory evaluation model of the public telework policy that, beyond the technical results, consider the real impact of public policy on the lives of public servants, workers, users in general, and their families. To this end, it uses a non-experimental and mixed methodology, combining qualitative and quantitative instruments such as direct observation, indirect and surveys that resulted in 519 responses to explore individual experiences and assess the effects of teleworking on skills, economy, health and routine. The results revealed that participation in the emancipatory evaluation of public policies faces challenges due to the lack of information and education on the subject, apathy and resistance on the part of higher organs, the lack of awareness of the impact these policies can have on people's lives, in addition to the fact that the public policy of telework in Ecuador does not adequately adapt to the diverse needs and perspectives of workers and users of Second Level health facilities in the city of Loja, generating negative impacts on equity and well-being.